Chronic Eosinophilic Leukaemia Presenting With A Cardiac Mass: A Case Report - Kabir, Ahmedul; Amin, Md Robed; Hasan, Pratyay; Mukerrama, Shegufta Mishket; Farhad, Muhammad Nurul; Deb, Sudip Ranjan; Hossain, Anwar (Bangladesh Journal of Medicine, 2015)
Chronic eosinophilic leukaemia is a rare disorder. It can cause irreversible target organ damage which can be life threatening,so early diagnosis of the disease is a necessity.It may pose as a diagnostic dilemma. Active consideration of the possibility of the disease is necessary. We intend to report a case of a boy of 13 years who presented with hepato-splenomegaly, generalized lymphadenopathy, a cardiac mass and a very high eosinophil count. He was ultimately diagnosed with chronic eosinophilic leukaemia.Though rare, this disease can occur in our country, too. Unavailability of confirmatory tests warrants more vigilance and awareness among physicians. Bangladesh J Medicine Jan 2014; 25 (1) : 25-28